Valproate and neuroprotective effects for bipolar disorder - Atmaca, Murad (Taylor & Francis Ltd, 2009)
Valproate is an anticonvulsant drug but also a mood stabilizer commonly used to treat bipolar disorder. It has a structure of short-chain fatty acid and is becoming a first line treatment for bipolar disorder. The effect mechanism of the vaproate has not been completely established but it has been suggested that alterations in gene expression may be involved in chronic treatment. On the other hand, a growing body of evidence emphasizes that valproate has neuroprotective and neurotrophic actions. Neuroimaging studies that examine neurochemistry in the living brain provide further support for the hypothesis that bipolar disorder is related to changes in neuronal viability and function. In cellular view of point, it was showed that valproate protected rat cerebral cortical and cerebellar granule cells from glutamate-related excitotoxicity, and apoptotic death of the endoplasmic reticulum in C6 glioma cells and PC 12 cells. At the genetic level, growing data suggest that the long-term treatment of mood disorders may involve the regulation of signalling pathways and gene expression in critical neuronal circuits. It has been shown that lithium and valproate produce some changes in basal and stimulated DNA binding to activator protein 1 (AP-1) transcription factors, considering that strategic changes in gene expression in critical neuronal circuits may be important in the treatment of a variety of psychiatric disorders. So, a growing body of evidence establishes its neuroprotective and neurotrophic actions in bipolar disorder.
Keywords: N-Acetyl-Aspartate; Signal-Transduction Pathways; Histone Deacetylase; Mood Stabilizer; Prefrontal Cortex; Lithium; Acid; Increases; Acetylaspartate; Spectroscopy